Biyani Guwiyang Dharug Ngurrawa: healing fire on Dharug Country - Dharug Ngurra; Lexodious Dadd; Corina Norman; Rebecca Scott; Lauren Tynan; Marnie Graham; Sandie Suchet-Pearson; Harriet Narwal; Jessica Lemire (Ecosystems and People, 2025)
Caring and attending to Dharug Ngurra (Indigenous Dharug Country in Sydney, Australia) is a deep responsibility that is part of Dharug Lore/Law. Though deeply impacted by ongoing colonisation processes, one important responsibility is to guwiyang (fire), which has burnt for and with Dharug people for all time. Through careful attention to guwiyang, this paper builds on the powerful work of Indigenous scholars to share our Yanama Budyari Gumada collective’s understandings of relationality through our work together at a special place on Dharug Ngurra called Yarramundi. We draw on the lessons learned from making buran nalgarra (stringybark rope) to highlight the difficult, complex, and messy relationships that can lie at the heart of relational practice, particularly in colonised places. We discuss how we navigate these tensions by focusing on the importance of ‘yanama budyari gumada’ (walking in good spirit), taking small steps, and learning from others on Dharug Ngurra. Guwiyang reveals how relational responsibilities require constant care and attention to Ngurra, and we engage the everyday politics of relationality on Dharug Ngurra to make a powerful case for recognition of Dharug regenerative sovereignties and the active support of Dharug custodians living on Ngurra—on lands and waters stolen by the British Crown. We speak not of relationality as a research method that can be discarded or ‘turned’ towards, but of relationality as life, as responsibility, as Dharug Ngurra. We argue that understanding and deeply engaging Indigenous relationalities is fundamental for sustainability research, practices, and thinking.